THE USE OF INNOVATIVE TECHNOLOGIES IN THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE FIELD OF SERVICES IN THE TRAINING AND PRODUCTION CLUSTER (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2020)
The article considers the effectiveness of the use of innovative technologies in the process of forming the professional competence of future service professionals in the educational and production cluster. Particular attention is paid to the emergence of new types and forms of organization of the educational process, in particular blended learning, due to the specifics of the cluster structure and systematic implementation in the training of future professionals of modern information and communication technologies. It was found that the use of interactive technologies in the educational and production cluster requires the transformation of the information infrastructure of all its participants, which is achieved through the use of common educational facilities, the creation of an innovative educational environment. The need to introduce interactive Smart-technologies as a means of creating, storing, transmitting, processing and managing information aimed at activating the creative potential of students has been proven. One of the most important directions of development of interactive technologies is considered - the MOODLE system which allows to create electronic training courses, to carry out full-time and distance learning. Emphasis is placed on the use of Google Forms cloud services, Microsoft Forms, designed to receive feedback. It was found that in the conditions of functioning of the cluster association the online method of teaching - webinar, in particular seminars, conferences, discussions, meetings, presentations, trainings, network broadcasts of various events became widely used. It is emphasized that in the educational process the participants of the cluster widely use the principles of BYOD as an additional source of information. The influence of each participant of the educational and production cluster on the formation of a set of competencies by means of information and communication technologies is determined.